2012
DOI: 10.1002/stem.1223
|View full text |Cite
|
Sign up to set email alerts
|

Nanog Reverses the Effects of Organismal Aging on Mesenchymal Stem Cell Proliferation and Myogenic Differentiation Potential

Abstract: Although the therapeutic potential of mesenchymal stem cells (MSC) is widely accepted, loss of cell function due to donor aging or culture senescence are major limiting factors hampering their clinical application. Our laboratory recently showed that MSC originating from older donors suffer from limited proliferative capacity and significantly reduced myogenic differentiation potential. This is a major concern, as the patients most likely to suffer from cardiovascular disease are elderly. Here we tested the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 53 publications
9
83
3
1
Order By: Relevance
“…Interestingly, this is also supported by the expression of Nanog, which is a transcription factor that inhibits differentiation and maintains the pluripotent capacity of embryonic and adult stem cells. 46 Therefore, a significantly higher Nanog expression implies that at least some of the MSC population still retained their primitive properties when they were maintained on the ECM-Col/HA scaffold. Taken together, these in vitro data suggest that the ECM-Col/HA scaffold promoted the proliferation, while retaining primitive MSCs, similar to the in vivo situation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this is also supported by the expression of Nanog, which is a transcription factor that inhibits differentiation and maintains the pluripotent capacity of embryonic and adult stem cells. 46 Therefore, a significantly higher Nanog expression implies that at least some of the MSC population still retained their primitive properties when they were maintained on the ECM-Col/HA scaffold. Taken together, these in vitro data suggest that the ECM-Col/HA scaffold promoted the proliferation, while retaining primitive MSCs, similar to the in vivo situation.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Whereas ectopic expression of NANOG enhanced proliferation of NIH-3T3 17,18 or bone marrow derived (BM)-MSCs, 1921 the effects of NANOG on differentiation are unclear and context-dependent. Terminal differentiation of myogenic progenitors into muscle was not affected by NANOG expression but transdifferentiation into osteocytes was impaired.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the G Model YSCDB-1531; No. of Pages 7 overexpression of Nanog, the other core ES cell pluripotency factor, was found to upregulate genes related to cell cycle control and DNA replication in mesenchymal stem cells, while also dedifferentiating them [72]. Along these lines, when analyzing the Sox2 interactome in ES cells, Gao et al [73] found that this factor is associated with the DNA replication machinery proteins Polb, Rpa1, Rpa2 and Rpa3.…”
Section: Pre-rc Member Links With Pluripotencymentioning
confidence: 99%